2022
DOI: 10.1007/s11920-022-01312-9
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior in the First Wave of the COVID-19 Pandemic

Abstract: Purpose of Review Since the declaration of the COVID-19 pandemic, there have been numerous social changes to try to ​​contain the spread of the disease. These sudden changes in daily life have also changed the way we relate to others, in addition to creating a climate of uncertainty and fear. Therefore, the objective of this review is to compile published data of the consequences of suicidal behavior in the first months from the onset of the pandemic. Recent Findings Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 113 publications
0
4
0
2
Order By: Relevance
“…Three studies found upward rebounds in post-lockdown periods [ 25 27 ], another found a downward rebound after loosening of restrictions[ 20 ]. A review by Giner et al focusing on the first 6 months of the pandemic found no overall change in suicidal behavior, although pointing out the preliminary nature of most included papers and that long term consequences may have an effect at a later phase of the pandemic [ 45 ]. In our sample, the first-wave but not the second-wave was an independent risk factor for all three suicidality outcomes (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three studies found upward rebounds in post-lockdown periods [ 25 27 ], another found a downward rebound after loosening of restrictions[ 20 ]. A review by Giner et al focusing on the first 6 months of the pandemic found no overall change in suicidal behavior, although pointing out the preliminary nature of most included papers and that long term consequences may have an effect at a later phase of the pandemic [ 45 ]. In our sample, the first-wave but not the second-wave was an independent risk factor for all three suicidality outcomes (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is considered the worst outcome or consequence of MDD, over 700,000 human lives are lost every year (Elias et al, 2022 ). Moreover, during the COVID‐19 pandemic, multiple challenges have arisen, such as loneliness or financial hardship, producing about 34% prevalence of depression in general population, with 5%–15% suicidal ideation in that period (Giner et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of this group is also emphasized by the observation that there was an increased psychiatric hospitalization rate for younger individuals during the pandemic [ 32 , 33 , 34 ]. In addition, younger people were also at an increased risk of committing suicide during this period [ 33 , 35 , 36 ]. This data further reinforces the findings that young people are particularly vulnerable to mental health disorders and suggests that they may need increased support during difficult times, such as during the pandemic and the associated social isolation.…”
Section: Discussionmentioning
confidence: 99%